Flipped Learning in Mathematics Classroom: A Systematic Literature Review - G.C., Laxmi (Brixton Scholarly Review, 2025)
Flipped learning has become increasingly popular in improving student’s achievement in mathematics. Flipped learning in a mathematics classroom is learning by doing thorough assessments out of the classroom or in the school. This research systematically reviewed the existing studies published between 2012 to 2023 (n=15). The finding of this study suggests that flipped learning is always effective for achievement, and involves discussion, self-learning, engagement, motivation, peer collaboration, and instructor feedback. FL approach provided better learning outcomes than the conventional approach. But, there are many challenges; such as; technological issues, lack of internet access, IT resources, and skills of FL. Thus, this review has recommended proposing a new model for effective flipped learning in the mathematics classroom.